Personal competency and behaviour effect on design judgement among designers in furniture manufacturing / Nor Hayati Mansor and Rahinah Ibrahim - Mansor, Nor Hayati; Ibrahim, Rahinah (Faculty of Art & Design, 2022)
Malaysia furniture manufacturing is a lucrative industry with the majority are Small and Medium Enterprises (SME). Moving the SMEs from Original Equipment Manufacturer (OEM) to Original Design Manufacturer (ODM) is encouraged by the government in pursuit of global competitiveness. One aspect of transformation is hiring design personnel into the manufacturing organization especially among the Bumiputra SMEs who are lagging behind the other manufacturer. The purpose of this study is to identify the qualities of designers who could improve design judgement for New Product Development (NPD) of furniture in their current operating context. This article is part of a series of studies in improving Bumiputra SMEs global competitiveness. This study in particular looks into aspects of the designer’s competencies and behavior that will affect design judgment. A survey was conducted on 33 designers who are employed from among 106 manufacturers registered with the Bumiputera furniture manufacturer organization of Malaysia. Statistical analyses including factor analysis, descriptive analysis, t-test, were employed to test relationships between dependent and independent variables. The study found personal skill, knowledge, ability, and experience representing designer’s personal competencies; and value, attitude, and trait representing designer’s personal behavior are critical in making appropriate design judgement. The results are expected to contribute to the development of a Designer Personal Competency Model for the furniture NPD process to help Bumiputra furniture SME manufacturers transform their OEM practice to ODM. This study is significant in supporting Malaysia economic growth specifically among Bumiputra SME manufacturers.